TMS 2016: 145<sup>th</Sup>Annual Meeting &Amp; Exhibition: Supplemental Proceedings 2016
DOI: 10.1002/9781119274896.ch23
|View full text |Cite
|
Sign up to set email alerts
|

Using Powder Cored Tubular Wire Technology to Enhance Electron Beam Freeform Fabricated Structures

Abstract: Electron Beam Freeform Fabrication (EBF 3 ) is an additive manufacturing technique, developed at NASA Langley Research Center, capable of fabricating large scale aerospace parts. Advantages of using EBF 3 as opposed to conventional manufacturing methods include, decreased design-toproduct time, decreased wasted material, and the ability to adapt controls to produce geometrically complex parts with properties comparable to wrought products. However, to fully exploit the potential of the EBF 3 process developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The size of grain β was reduced from 1164 μm to 734 μm. D. Gonzales et al [15] demonstrated that the use of flux-cored wires containing more aluminium, iron and boron enabled the making of elements of titanium alloy Ti-6Al-4V characterised by more stable and more refined microstructure. S. Phinazee [16] performed rapid prototyping tests involving the use of electron beam aimed to make an airframe element of titanium alloy Ti-6Al-4V and stated that the abovenamed process made it possible to reduce the consumption of material by 79% and the cost of manufacturing from 17 430 to 9 810 USD.…”
Section: Electron Beam Rapid Prototypingmentioning
confidence: 99%
“…The size of grain β was reduced from 1164 μm to 734 μm. D. Gonzales et al [15] demonstrated that the use of flux-cored wires containing more aluminium, iron and boron enabled the making of elements of titanium alloy Ti-6Al-4V characterised by more stable and more refined microstructure. S. Phinazee [16] performed rapid prototyping tests involving the use of electron beam aimed to make an airframe element of titanium alloy Ti-6Al-4V and stated that the abovenamed process made it possible to reduce the consumption of material by 79% and the cost of manufacturing from 17 430 to 9 810 USD.…”
Section: Electron Beam Rapid Prototypingmentioning
confidence: 99%